Spatial proximity and location dynamics of knowledge-intensive business service in the Pearl River Delta, China. (April 2016) - Wang, Jiejing; Zhang, Xiaohu; Yeh, Anthony G.O.
Abstract: Western studies on location dynamics of knowledge-intensive business services (KIBS) suggest that KIBS firms tend to locate proximally to multinational enterprises and already established KIBS firms. This paper examines the location dynamics of KIBS firms in the Pearl River Delta (PRD) of China, one of the manufacturing centers and fastest-growing global mega-city regions in the world. This study reveals that KIBS in the PRD have become more spatially concentrated from 2004 to 2008. Both state-owned enterprises (SOEs) and foreign-owned enterprises (FOEs), two dominant players in the regional economy, play a positive role in attracting KIBS-births. This indicates that the presence of SOEs and FOEs has significantly shaped the location patterns of KIBS firms in the PRD, and the influence of SOEs is even stronger than that of the FOEs. Moreover, the new KIBS firms tend to co-locate with existing KIBS firms, which confirms that the cumulative causation mechanism matters in new KIBS firm formation process in the PRD. Other contextual factors, such as the state-governed developing zones (DZs), also have positive effects on KIBS-births. These findings suggest that more attention should be paid to the role of the state in restructuring the economic landscape of China where a mature market economy system is still lacking, although there are increasing signs of the influence of global firms.